Cardiomyocyte membrane structure and cAMP compartmentation produce anatomical variation in β2AR-cAMP responsiveness in murine hearts - Wright, PT; Bhogal, NK; Diakonov, I; Pannell, LMK; Perera, RK; Bork, NI; Schobesberger, S; Lucarelli, C; Faggian, G; Alvarez-Laviada, A; Zaccolo, M; Kamp, TJ; et al. (Elsevier, 2018)
Cardiomyocytes from the apex but not the base of the heart increase their contractility in response to β2-adrenoceptor (β2AR) stimulation, which may underlie the development of Takotsubo cardiomyopathy. However, both cell types produce comparable cytosolic amounts of the second messenger cAMP. We investigated this discrepancy using nanoscale imaging techniques and found that, structurally, basal cardiomyocytes have more organized membranes (higher T-tubular and caveolar densities). Local membrane microdomain responses measured in isolated basal cardiomyocytes or in whole hearts revealed significantly smaller and more short-lived β2AR/cAMP signals. Inhibition of PDE4, caveolar disruption by removing cholesterol or genetic deletion of Cav3 eliminated differences in local cAMP production and equilibrated the contractile response to β2AR. We conclude that basal cells possess tighter control of cAMP because of a higher degree of signaling microdomain organization. This provides varying levels of nanostructural control for cAMP-mediated functional effects that orchestrate macroscopic, regional physiological differences within the heart.